A qualitative study of perceptions of senior health service staff as to factors influencing the development of Advanced Clinical Practice roles in mental health services. Issue 5 (27th August 2021) - Brimblecombe, Neil; Nolan, Fiona
Accessible Summary: What is known on the subject?: Advanced clinical practitioners (ACPs) are, typically, non‐medical healthcare professionals, who possess advanced clinical skills, a master's level qualification and evidence of leadership, management and research abilities. Most ACPs are nurses and new ACP roles are increasingly being established around the world. The views of senior staff towards new mental health nursing roles in organizations are likely to influence their introduction and sustainability Research on mental health nursing ACP roles is sparse. What the paper adds to existing knowledge?: The paper uniquely provides specific information as to factors perceived by senior staff as affecting the implementation of ACP roles in mental health services. A wide range of mental health services were perceived as potentially benefiting from ACPs. Establishing role clarity for MHN ACPs is perceived as being as essential to successful introduction of the role, as has been found for other specialities. What are the implications for practice?: Participants identified a need for early engagement with service users and professions about new ACP roles and for processes that can evaluate ACP roles once they established. Some mental health nurses may require long‐term developmental pathways to help prepare them to take on a master's level course and then the ACP role. Abstract: Introduction: Advanced clinical practice (ACP) roles are increasingly being developed internationally. Identifying factors perceived as affecting the development of ACP can support effective implementation. Aim: To understand the views of senior health service staff as to factors influencing the development of ACP roles in mental health services. Method: Focus group and semi‐structured interviews. Participants were directors of nursing (n = 10) and other senior staff from roles important to workforce development (n = 10). Results: Content analysis suggested seven categories: understanding the role and national guidelines, attitudes to the role, learning from implementing other roles, understanding prerequisites for development, challenges, opportunities and future support/actions. Prerequisites for success would include early engagement with stakeholders. Medical attitudes towards ACP roles were perceived as generally more positive than previously. Discussion: The study provides unique information regarding perspectives of senior staff regarding the implementation of ACP roles in mental health services. A wide range of mental health services were perceived as potentially benefiting from ACPs, with the importance of role clarity being highlighted and long‐term developmental pathways for staff. Implications for practice: Successful Implementation of ACP roles may require clear role definition, early engagement with stakeholders and processes to evaluate role outcomes.